Bone marrow stromal cells induce changes in pain behavior after sciatic nerve constriction - Musolino, Patricia Leonor (2007)
Peripheral nerve injury, i.e. a single ligature nerve constriction (SLNC), triggers neuropathic pain. Bone marrow stromal cells (MSCs) have been observed to migrate to the injured tissues and mediate functional recovery following brain, spinal cord and peripheral nerve lesions. We have recently shown MSC selective migration to the ipsilateral lumbar (L3-6) dorsal root ganglia (DRGs) after a sciatic nerve SLNC. In this study, we have analyzed the thermal and mechanical sensitivities of animals subjected to a SLNC of the sciatic nerve and an ipsilateral intraganglionic MSC injection, using the von Frey and Choi tests. Control animals were subjected to the nerve lesion either alone or followed by the administration of phosphate-buffered saline (PBS) or bone marrow non-adherent mononuclear cells (BNMCs). All the animals were tested both before surgery and after 1, 3, 7, 14, 21, 28 and 56 days. Animals subjected to the sciatic nerve constriction developed ipsilateral mechanical and thermal allodynia already 3 days after the lesion. The allodynic responses were maintained even after 56 days. MSC administration prevented the generation of mechanical allodynia and reduced the number of allodynic responses to cold stimuli. On the contrary, the injection of either PBS or BNMCs could not counteract allodynia. These results suggest that MSCs may modulate pain generation after sciatic nerve constriction. The underlying mechanisms by which MSCs exert their actions on pain behavior need to be clarified.